Pengembangan Sistem Informasi Manajemen Kegiatan Sekolah berlandaskan Penguatan Pendidikan Karakter di SMP Islam Sabilurrosyad Malang - Muhammad Zhafran Auristianto; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Reinforcement Program of Character Education or PPK is a program that has been stated on the Presedential of the Indonesian Republic decree number 87 in year 2017 for Reinforcement Program of Character Education . The goal for Reinforcement Program of Character Education is to build students character for the golden generation. Islamic Junior High School of Sabilurrosyad is one of the Junior High School that is located in Malang that uses Reinforcement Program of Character Education as a foundation for organizing activites. Activites that the school have been doing are creating an activity proposal which follows through the creation of a documentation of a finished activity. These activites are still conducted manually, so that the documentation of every activity that has already been executed will be put into a book. But, some of the documentations are missing when the school staff wanted to merged the documentation into a book. After completing all of the school activities, the school will be conducting assessment according to Reinforcement Program of Character Education . Therefore, from the problems that have been told, can be conducted a research to build an information system that can facilitate activity management and user accounts for the school to use. Development of this system is based on iterative development, and the system is build using Laravel version 6 within two iterations. Each series of iterations are tested using validation testing with all results are valid and compatibility testing with pretty good results in every browser available.